The effects of lockdown on lifestyle habits of adults during the coronavirus pandemic in Cyprus - Philippou, E (Eur J Public Health, 2020)
BACKGROUND: Despite widespread adoption of lockdown by governments in the COVID-19 response, research on how it affects the individual pillars of Lifestyle Medicine is limited. We aimed to explore the effects of COVID-19 lockdown on healthy eating, physical activity, sleep, stress, social support and use of risky substances. METHODS: This was a cross-sectional study on a convenient sample of adults who resided in Cyprus during the lockdown. An anonymous questionnaire was completed online in Greek or English comprised of five validated tools in relation to their behaviours before and during the lockdown. We compared median values for each variable/tool before and during lockdown, using Wilcoxon Signed Rank test, and performed stratified analyses for sociodemographic characteristics. RESULTS: Out of 745 respondents, 74% were female and median age was 39. Overall scores showed significantly increased sleep quality difficulty (4 v 5, p < 0.001), decreased social support (71 v 68, p < 0.001), and increased perceived stress (22 v 25, p < 0.001) between February 2020 and the month in lockdown. Mediterranean diet adherence increased significantly only in those who followed religious fasting during lockdown (6 v 7, p < 0.001). Total minutes spent sitting significantly increased (120 v 180, p < 0.001) although overall physical activity score did not significantly change. Smoking intensity (daily number of cigarettes and e-cigarettes) as well as frequency of alcohol consumption (daily number of drinks) increased significantly (p trend=0.029 and <0.001, respectively). CONCLUSIONS: Many aspects of lifestyle were adversely affected by lockdown in Cyprus. As people return to their pre-lockdown routines, the outcomes described provide data to inform the design of lifestyle interventions that support changing or maintaining lifestyle habits. Such interventions can then help decrease people's risk for future poor health outcomes, including the risk for COVID-19 infection. KEY MESSAGES: This study describes aspects of lifestyle affected by the Cyprus COVID-19 lockdown, significant when considering future lockdowns and pre-, during or post-lockdown healthful lifestyle interventions. The outcomes provide data to inform the design of lifestyle interventions to support changing or maintaining healthy lifestyle habits.